Intrahepatic TH17/TReg Cells in Homeostasis and Disease-It's All About the Balance - Hannah K. Drescher; Lea M. Bartsch; Sabine Weiskirchen; Ralf Weiskirchen (Frontiers Media S.A., 2020)
Both acute and chronic hepatic inflammation likely result from an imbalance in the TH1/TH2 cell response and can lead to liver fibrosis and end-stage liver disease. More recently, a novel CD4+ T helper cell subset was described, characterized by the production of IL-17 and IL-22. These TH17 cells 50were predominantly implicated in host defense against infections and in autoimmune diseases. Interestingly, studies over the last 10 years revealed that the development of TH17 cells favors pro-inflammatory responses in almost all tissues and there is a reciprocal relationship between TH17 and TReg cells. The balance between TH17and TReg cells is critical for immune reactions, especially in injured liver tissue and the return to immune homeostasis. The pathogenic contribution of TH17 and TReg cells in autoimmunity, acute infection, and chronic liver injury is diverse and varies among disease etiologies. Understanding the mechanisms underlying TH17 cell development, recruitment, and maintenance, along with the suppression of TReg cells, will inform the development of new therapeutic strategies in liver diseases. Active manipulation of the balance between pathogenic and regulatory processes in the liver may assist in the restoration of homeostasis, especially in hepatic inflammation.